The Influence of lecturers’ verbal and non-verbal immediacy behaviour on perceived affective and cognitive learning in a multicultural context. (Communicare: Journal for Communication Studies in Africa, 2022)
The intention of the present study was to determine whether (1) the immediacy behaviourof lecturers whose home language is Afrikaans or English contributes positively to theaffective and cognitive learning of learners whose home language is Afrikaans, Englishor one of the African languages; and (2) whether the form of immediacy behaviourdisplayed by English or Afrikaans lecturers functions differently for learners whose homelanguage is one of the African languages in relation to those whose home language isAfrikaans or English. Data was collected by means of a questionnaire that had separatesections on immediacy behaviour and learning. Positive correlations between theimmediacy behaviour of the lecturers and the affective and cognitive learning of thelearners were observed for the whole test group. The immediacy behaviour displayed bythe lecturers functions differently for learners whose home language is one of the Africanlanguages than for those whose home language is Afrikaans or English. Considering thesefindings, it is imperative that instructional communication in today’s South Africa beincreasingly characterized by a culture-centred approach.